Health professionals’ perceptions, barriers and knowledge towards oral health care of dependent people in nursing homes: a systematic review - Joana Pombo-Lopes; Inês Rodrigues; Joana Costa; Ana Catarina Gomes; Jorge Fonseca; Jorge Fonseca; José Grillo-Evangelista (Frontiers in Public Health)
IntroductionThis review aimed to evaluate the perceived barriers, knowledge, and training, of different health care professionals in relation to the oral health of dependent people in nursing homes and access, as well, how this data was evaluated.MethodsThree electronic databases—PubMed/MEDLINE, Web of Science, and LILACS—were searched independently by two researchers for relevant studies published up to December 2023. Articles were selected according to the established inclusion and exclusion criteria, and a total of 35 studies were included.ResultsFindings from the Nursing Dental Coping Belief Scale studies revealed disparities between training and daily oral health care, with experienced nurses experiencing challenges. Barriers described were categorized and included resident-related issues, organizational challenges, and caregiver-related difficulties. Most caregivers reported inadequate training, often informal or experiential, although they are involved in the hygiene of the older adult, with tooth brushing and denture cleaning being the most common practices. Low oral health literacy coexisted with recognition of the importance of oral health care.ConclusionThe findings advocate for targeted interventions, standardized training, and improved support systems to improve oral health care for the older adult in diverse health care settings.